2018
DOI: 10.1007/s00497-018-0338-1
|View full text |Cite
|
Sign up to set email alerts
|

Seed tissue and nutrient partitioning, a case for the nucellus

Abstract: Flowering plants display a large spectrum of seed architectures. The volume ratio of maternal versus zygotic seed tissues changes considerably among species and underlies different nutrient-storing strategies. Such diversity arose through the evolution of cell elimination programs that regulate the relative growth of one tissue over another to become the major storage compartment. The elimination of the nucellus maternal tissue is regulated by developmental programs that marked the origin of angiosperms and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…Despite the fact that nucellus development varies between species, the functional significance of intra- and inter-species variation in nucellus size has remained unclear (Rudall et al, 2005; Rudall et al, 2008; Endress 2011; Lu and Magnani 2018). In cereals, hypotheses suggest that a bigger nucellus might provide a larger repository of amino acids, carbohydrates, or hexose sugars that are required for the early stages of grain development (Wilkinson et al, 2018), but this has yet to be conclusively shown.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that nucellus development varies between species, the functional significance of intra- and inter-species variation in nucellus size has remained unclear (Rudall et al, 2005; Rudall et al, 2008; Endress 2011; Lu and Magnani 2018). In cereals, hypotheses suggest that a bigger nucellus might provide a larger repository of amino acids, carbohydrates, or hexose sugars that are required for the early stages of grain development (Wilkinson et al, 2018), but this has yet to be conclusively shown.…”
Section: Discussionmentioning
confidence: 99%
“…The nucellus is a tissue of maternal origin that gives rise to and supports the early female gametophyte and developing seed, and in many species degenerates through PCD (Lu and Magnani, 2018). In aubergine (Solanum melongena), a putative cysteine protease similar to tobacco's has been identified and is expressed in nucellar cells as well as in several other tissue types that undergo PCD (Xu and Chye, 1999).…”
Section: Proteases In Seed Integument and Nucellus Pcdmentioning
confidence: 99%
“…Mainly in stage 6 (open flower), several genes belonging to proteases (e.g., METACASPASE9 and SUBTILASES), nucleases (e.g., ENDONUCLEASE), and cell wall modifying enzymes (e.g., ENDOGLUCANASE and b-GLUCOSIDASE) are strongly upregulated in jai1-1 ovules ( Figure 2D). It is possible that the enzymes encoded by these genes might mediate morphological changes in jai1-1 ovules, since proteases and nucleases have been implicated in nucellus degeneration by PCD (Lu and Magnani, 2018). Therefore, ovule morphology was analyzed in carpel cross sections ( Figure 3).…”
Section: Jasmonate-insensitivity Alters the Transcriptome In Ovulesmentioning
confidence: 99%
“…The maternal tissue of the ovule also undergoes drastic changes, such as a rapid phase of cell division and expansion in the integuments (Haughn and Chaudhury, 2005). In several plant species, the proximal region of the nucellus undergoes programmed cell death (PCD) and partially or totally disappears (Lu and Magnani, 2018).…”
Section: Introductionmentioning
confidence: 99%